Alkali metal silanides α-MSiH3: A family of complex hydrides for solid-state hydrogen storage. (27th April 2017) - Zhang, J.; Yan, S.; Qu, H.; Yu, X.F.; Peng, P.
Abstract: The alkali metal silanides α -MSiH3 appear to be a promising family of complex hydrides for solid-state hydrogen storage. Herein the structural, energetic and electronic properties of α -MSiH3 silanides (M = Li, Na, K, Rb, Cs) and MSi Zintl phases are systematically investigated for the first time by using first-principles calculations method based on density functional theory. The structural parameters of α -MSiH3 and MSi including lattice constants and atomic positions are determined through geometry optimization. The obtained results are close to the experimental data analysed from X-ray and neutron powder diffraction. The calculations of formation enthalpy show that α -KSiH3, α -RbSiH3 and α -CsSiH3 silanides are easier to be synthetized relative to α -LiSiH3 and α -NaSiH3, which interprets well the lower thermostabilities of experimental α -LiSiH3 and α -NaSiH3 . Nevertheless, LiSi, KSi and CsSi phases are easier to be formed relative to NaSi and RbSi. The calculations of hydrogen desorption enthalpy reveal that the dehydrogenation abilities of α -MSiH3 silanides along the decomposition path of α -MSiH3 →MSi + H2 are gradually enhanced in the order of α -CsSiH3, α -RbSiH3, α -KSiH3, α -NaSiH3 and α -LiSiH3, which may be originated from their decreasing thermostabilities. From a comprehensive point of view including hydrogen storage capacity, thermostability and dehydrogenation ability, α -KSiH3 (∼4.29 wt%) is identified as the most promising alkali metal silanide for reversible hydrogen storage. Analysis of electronic structures indicates that a significant charge transfer leads to positively charged M ions and negatively charged SiH3 complex, which constitutes the ionic bonding between them. The bonding within SiH3 complex not only involves the covalent hybridization between Si (3s) (3p) and H (1s) orbitals, but also exhibits some ionic bond characteristics due to the partial charge transfer from Si to H. The covalent bonding interactions between H and Si atoms within SiH3 mainly dominate the thermostabilities and dehydrogenation properties of α -MSiH3 silanides. Graphical abstract: Highlights: Structural parameters of α -MSiH3 silanides and MSi Zintl phases are determined. α -KSiH3, α -RbSiH3 and α -CsSiH3 are easier to be formed than α -LiSiH3 and α -NaSiH3 . LiSi, KSi and CsSi are easier to be synthesized than NaSi and RbSi. Dehydrogenation ability is enhanced in the order of Cs, Rb, K, Na and Li silanide. Covalent bonding between H and Si dominates thermostability of α -MSiH3 .